Peningkatan Kemampuan Menulis Karangan Narasi Menggunakan Model Kooperatif Tipe Examples Non Examples Di Kelas IV SDN 10 Teratak Tempatih - Oksrinawati, Oksrinawati (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
Abstract : This Research was intended to  improve the ability write naration essay by using kooperatif tipe Example Non Example learning model in the four grade of SDN.10 Teratak Tempatih. The subject of the research was the  four grade students of SDN 10 Teratak Tempatih. The results of reseach showed that from the first cycle from teachers to the second one, the score of the lesson plan improved from 75. On student aspect of student having skors 71,59, stage of writing with avarenge value 78,04.while the observation of cycle the secont two from the aspect of teacher 88,64,in the aspect of students 91.67,research of the second cycle in the averange score 80,00 the writing stage obtains 72,22 ,at the  post writing stage obtains 84,00.thus the cooperative learning model Example Non Example in SDN 08 Teratak tempatih efectively improved the student’s learning achievement in narrative essay.Keywords: write naration essay, Student Class IV SD